2020
DOI: 10.1101/2020.02.21.959213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Planar cell polarity in the larval epidermis ofDrosophilaand the role of microtubules

Abstract: 10We investigate the mechanisms of planar cell polarity (PCP) in the larval epidermis of 11 Drosophila. Measurements of the amount of Dachsous across the segment find a peak 12 located near the rear of the anterior compartment. Localisation of Dachs and 13 orientation of ectopic denticles reveal the polarity of every cell in the segment. We 14 discuss how well these findings evidence a zigzag gradient model of Dachsous activity. 15 Several groups have proposed that Dachsous and Fat fix the direction of PCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Namely, we demonstrated that the overall direction of microtubules follows the cell's long axis whereas the alignment of microtubules with each other is consistent with the cell eccentricity in agreement with the robustness of this alignment previously reported (Płochocka et al, 2021). A similar role for cell shape in organising microtubule polarity independently of Ft-Ds polarity has also been suggested in the Drosophila larval epidermis (Pietra et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…Namely, we demonstrated that the overall direction of microtubules follows the cell's long axis whereas the alignment of microtubules with each other is consistent with the cell eccentricity in agreement with the robustness of this alignment previously reported (Płochocka et al, 2021). A similar role for cell shape in organising microtubule polarity independently of Ft-Ds polarity has also been suggested in the Drosophila larval epidermis (Pietra et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…Within the A compartment, about two rows of the most anterior cells (figure 5 c ) and about two rows of the most posterior cells (figure 5 d ) show D located posteriorly; thus, their Ds/Ft polarity is that normally characteristic of the P cells. The third instar larva, having fewer but larger polyploid cells told a similar story: a set of cells in the A compartment, those confined to the extreme posterior row, had variable polarity with some showing the same polarity as in the P compartment (D accumulating posteriorly, [40]).
Figure 5Asymmetric localization of Dachs vis-à-vis A/P boundary.
…”
Section: Resultsmentioning
confidence: 99%
“…Ft–Ds may also regulate microtubule orientation and core protein polarity in the anterior compartment of the abdomen. Here, microtubule plus-end growth is weakly biased towards the posterior ends of cells [54], although predominantly growth is along the mediolateral axis of the abdomen, orthogonal to the axis of asymmetry [129]. Consistent with this slight plus-end bias, Dsh particles show a posterior bias in their transport, as expected from the axis of the polarity of the core proteins [54].…”
Section: Indirect Effects Of Ft and Ds On Core Protein Localizationmentioning
confidence: 94%
“…The core proteins localize asymmetrically to anterior–posterior cell edges, but loss of core protein activity has relatively little effect on denticle orientation [107,134136]. However, in the embryo and larva, denticle polarity correlates with asymmetric localization of Ds and D [129,137,138], and loss or overexpression of Ft–Ds severely disrupts denticle belt polarity [107,136139]. Fj is highly expressed in the tendon cells which are posterior to rows 1 and 4 in the larval epidermis, which may explain the pattern of denticle polarity [140].…”
Section: Polarization Of Cuticular Structures By Ft–ds Independently ...mentioning
confidence: 99%
See 1 more Smart Citation